Elucidation of the shanorellin biosynthetic pathway and functional analysis of associated enzymes. Issue 3 (31st October 2014) - Sato, Michio; Yamada, Haruka; Hotta, Kinya; Watanabe, Kenji
Abstract : Since fungal natural products biosynthesized by polyketide synthases frequently exhibit useful biological activities, identifying and understanding the mechanism of biosynthetic steps taken by PKSs are of great interest. Abstract : Since fungal natural products biosynthesized by polyketide synthases frequently exhibit useful biological activities, identifying and understanding the mechanism of biosynthetic steps taken by PKSs are of great interest. One such compound isolated from Chaetomium globosum is shanorellin, whose biosynthetic gene cluster was activated by overexpressing the transcription factor, CgsG. Through targeted gene knockout in C. globosum and in vitro biochemical analyses, we determined for the first time the gene cluster and the pathway for the biosynthesis of shanorellin. We also identified that cytochrome P450 CgsB is responsible for catalysing hydroxylation of a methyl group at C5 in the aromatic product biosynthesized by CgsA. Subsequently, flavin-containing monooxygenase CgsF affects decarboxylation of the intermediate to form the quinone product, shanorellin. While this class of natural products exhibit notable biological activities, silencing of relevant gene clusters in the producing organisms results in trace-level production of those compounds under conventional culture conditions. Overexpression of the biosynthetic gene cluster's transcription regulator was achieved by incorporating a regulatable promoter into the native fungal genome. This approach allowed us to identify the shanorellin gene cluster and decipher its biosynthetic pathway effectively.